فعالية الطريقة المباشرة في تعليم مهارة الكلام لطلاب معهد دار السلام كونتور الحرم الحادى عشر اتحاد الأمة فوسو سولاوسى الوسطى: فعالية الطريقة المباشرة في تعليم مهارة الكلام لطلاب معهد دار السلام كونتور الحرم الحادى عشر اتحاد الأمة فوسو سولاوسى الوسطى - Ahsan, Amir; Abdul Qahar Zainal; Wahyuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the direct method in teaching speaking skills to the students of Darussalam Gontor Islamic Boarding Scool Campus Eleventh Ittihadul Ummah Poso Central of Sulawesi. Using a quantitative approach, data were collected through observation, interviews, questionnaires, and documentation analysis. The results showed that the direct method had a significant impact on improving speaking skills, with an effectiveness rate of 76.23%, which is categorized as "influential." Statistical analysis also revealed a strong and significant correlation (regression coefficient 0.815 and coefficient of determination 51.6%), indicating that the direct method plays a crucial role in developing students' speaking abilities. These findings confirm that the direct method is highly effective in enhancing Arabic speaking skills and can be recommended as an appropriate approach in Arabic language teaching.